Lipid Biosynthetic Genes Affect Candida albicans Extracellular Vesicle Morphology, Cargo, and Immunostimulatory Properties - Wolf, Julie M. (Eukaryot Cell, 2015)
Microbial secretion is integral for regulating cell homeostasis as well as releasing virulence factors during infection. The genes encoding phosphatidylserine synthase (CHO1) and phosphatidylserine decarboxylase (PSD1 and PSD2) are Candida albicans genes involved in phospholipid biosynthesis, and mutations in these genes affect mitochondrial function, cell wall thickness, and virulence in mice. We tested the roles of these genes in several agar-based secretion assays and observed that the cho1Δ/Δ and psd1Δ/Δ psd2Δ/Δ strains manifested less protease and phospholipase activity. Since extracellular vesicles (EVs) are surrounded by a lipid membrane, we investigated the effects of these mutations on EV structure, composition, and biological activity. The cho1Δ/Δ mutant releases EVs comparable in size to wild-type EVs, but EVs from the psd1Δ/Δ psd2Δ/Δ strain are much larger than those from the wild type, including a population of >100-nm EVs not observed in the EVs from the wild type. Proteomic analysis revealed that EVs from both mutants had a significantly different protein cargo than that of EVs from the wild type. EVs were tested for their ability to activate NF-κB in bone marrow-derived macrophage cells. While wild-type and psd1Δ/Δ psd2Δ/Δ mutant-derived EVs activated NF-κB, the cho1Δ/Δ mutant-derived EV did not. These studies indicate that the presence and absence of these C. albicans genes have qualitative and quantitative effects on EV size, composition, and immunostimulatory phenotypes that highlight a complex interplay between lipid metabolism and vesicle production.